Yablo on subject-matter. - Fine, Kit (Philosophical Studies, 2020)
I discuss Yablo's approach to truthmaker semantics and compare it with my own, with special focus on the idea of a proposition being true of or being restricted to some subject-matter, the idea of propositional containment, and the development of an 'incremental' semantics for the conditional. I conclude with some remarks on the relationship between truth-maker approach and the standard possible worlds approach to semantics.